Efek Kinerja Keuangan Dan Kebijakan Keuangan Terhadap Nilai Perusahaan - Agoestina Mappadang; Jusuf Luther Mappadang; Agustinus Miranda Wijaya (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
This study is aimed to examine the effect of financial performance and financial policy using variables the Return on Equity (ROE), Return on Assets (ROA), Firm Size (SIZE), Debt to Equity Ratio (DER), and Earning per Share (EPS) towards firm value indicated by Price to Book Value (PBV) of plantation sector companies listed in the Indonesia Stock Exchange. The data is obtained from the company's financial statements for the 2016-2020 consecutive year. The data was processed using Multiple Regression Analysis with SPSS 25. The results showed that profitability indicated by return on equity (ROE) had a positive and significant effect on the firm value indicated by Price to Book Value (PBV). Return on Assets (assets) has a positive and significant effect on firm value as indicated by Price to Book Value (PBV). Firm size has a positive but non-significant effect on firm value. The debt to Equity Ratio has a significant negative effect on firm value. Earning per share has a positive and significant effect on firm value. Simultaneously, Return on Equity (ROE), Return on Assets (ROA), Company Size (SIZE), Debt to Equity Ratio (DER), and Earning per Share (EPS) has a significant effect on firm value as indicated by Price to Book Value ( PBV)